PENGARUH BUDAYA ORGANISASI, STRES KERJA, LOCUS OF CONTROL TERHADAP KINERJA PEGAWAI: KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Fitri Agustina; Dian Mustika; Riza Dwi Andarini (Universitas Teknokrat Indonesia, 2022)
This purpose of this study is to examine and determine the effect of organizational culture, job stress, locus of control on employee performance by using job satisfaction as a mediating variable. This research is quantitative research based on a survey method using a questionnaire as a media for data collection, with 68 respondents obtained in the Regional Government Organization of Tulang Bawang Regency in 2021. The data collection technique used in this study was purposive sampling. The data analysis and hypothesis testing methods used SMARTPLS 3.0 software. The results of this study indicated that organizational culture had an effect on employee performance, job stress, and locus of control had no effect on employee performance; On the other hand, job satisfaction is able to mediate the relationship between the influence of organizational culture and work pressure on employee performance, while job stress is not able to mediate the influence of locus of control on employee performance.